Austrian outbound foreign direct investment in Europe: A spatial econometric study - Nico Pintar; Benedikt Sargant; Manfred M. Fischer (European Regional Science Association (ERSA), 2016)
The recent growth in foreign direct investment (FDI) has led to a proliferation of scholarly efforts to analyse the various dimensions of this phenomenon. Two main streams of research have emerged in the literature. The first analyses the economic effects of FDI inflows in the economy of the host countries, whereas the second studies the economic factors/conditions in the host countries that pull in FDI flows. The purpose of this paper is to add to this latter dimension of the literature. Most empirical models on the determinants of FDI have used a two-country framework and assumed that the decisions of a multinational enterprise to invest in a particular host country is independent of the decision whether or not to invest in any other country. But there are a number of theoretical reasons why FDI inflow into a host country may depend on the FDI in approximate countries. Such spatial interdependence has been largely neglected in the empirical literature, with notable exceptions of Baltagi et al. (2007), Blonigen et al. (2007), and Regelink and Elhorst (2015) for US outbound FDI, and Garretsen and Peeters (2009) for Dutch outbound FDI. The objective of this study is to test for the relevance of spatial relationships in Austrian outbound foreign direct investment flows to European countries. We estimate spatial Durbin models with fixed effects for Austrian FDI to 26 host countries. Third-country effects enter the models in two ways: first, by including an endogenous spatial lag on FDI (measured by FDI into markets nearby the host country), and by extending the set of explanatory variables with an exogenous market potential variable (measured by the size of markets nearby the FDI host country, in terms of gross domestic product). The question whether the empirical results are consistent with horizontal, vertical, export-platform or complex vertical FDI then depends on the signs and significance levels of the impact estimates of these two variables.
Keywords: C21; F21; 330; Foreign direct investment; spatial econometrics; spillover effects; fixed effects